Machine learning-guided optimization of lignocellulose-derived biochar precursors with tailored properties for energy storage applications - Alireza Shafizadeh; Nilofar Najafi; Ehsan Kargaran; Meysam Madadi; Mahdy Elsayed (Fuel, 2026)

Integrated hydroponics systems with anaerobic biogas slurry: Analysis of nitrified bio slurry, plant growth performance, and human health risk assessment - Tarek Mahrous; Ping Ai; Ali Abd-Elkader; Aibin Hu; Mahdy Elsayed (Bioresource Technology Reports, 2026)

Maternal high-fat diet and its multigenerational impact on hypertension and metabolic alterations in Wistar rat offspring - Maghawry Hegazy; Mahmoud Mohamed Mokhtar; Elsayed G. E. Elsakka; Hesham A. El-Mahdy; Samy Y. Elkhawaga; Mohamed A. Elkady; Amr Mohamed Yehia; Ahmed Aglan; Ahmed M. Mansour; Salama Abdo Salama; Hamada Ahmed Mokhlis; Hesham Fathy Hassan; et al. (Journal of Molecular Histology, 2026)

Valorization of abattoir water discharge through phycoremediation for enhanced biomass and biodiesel production - Mahdy Elsayed; Yevheniia Mysnyk; Mohamed Mahmoud-Aly; Ehab Mostafa; Adel W. Almutairi; Doaa G. Abbas; Mohamed M. Ibrahim; Dieter Hanelt; Abdelfatah Abomohra (Biomass and Bioenergy, 2024)

Upcycling furfural residues into bioethanol and pyrolytic oil through a cascading biorefinery approach - Mahdy Elsayed; Meysam Madadi; Guojie Song; Zhihui Zhou; Huijun Wang; Jing Wang; Junhui Zhang; Mortaza Aghbashlo; Meisam Tabatabaei (Fuel, 2024)

A sustainable, zero-waste approach for production of biohydrogen from chicken manure slurry by hybrid recycling of digestate - Mohamed Eraky; Mahdy Elsayed; Ai Ping; Zhang Tangjuan; Yao Yiqing; Nian Liu; Ahmed Tawfik (Chemical Engineering Journal, 2024)

Unraveling the mechanisms underlying lignin and xylan dissolution in recyclable biphasic catalytic systems - Xiuchao Xie; Meysam Madadi; Salauddin Al Azad; Yanming Qiao; Mahdy Elsayed; Mortaza Aghbashlo; Meisam Tabatabaei (Fuel, 2024)

From diagnosis to resistance: a symphony of miRNAs in pheochromocytoma progression and treatment response - Elsayed G. E. Elsakka; Ahmed Elshafei; Mohamed A. Elkady; Amr Mohamed Yehia; Ahmed I. Abulsoud; Reem K. Shahin; Nourhan M. Abdelmaksoud; Samy Y. Elkhawaga; Ahmed Ismail; Mahmoud Mohamed Mokhtar; Mahmoud A. Elrebehy; Maghawry Hegazy; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Sustainable valorization of waste glycerol into bioethanol and biodiesel through biocircular approaches: a review - Mahdy Elsayed; Mohamed Eraky; Ahmed I. Osman; Jing Wang; Mohamed Farghali; Ahmed K. Rashwan; Ibrahim H. Yacoub; Dieter Hanelt; Abdelfatah Abomohra (Environmental Chemistry Letters, 2024)
Liquid biofuels like biodiesel and bioethanol are crucial in the transition to low-carbon and high-energy alternatives to fossil fuels. One significant by-product of biodiesel production is glycerol, which accounts for about 10% of the total conversion output. While waste glycerol poses challenges due to its impurities and contaminants, it also holds potential as a metabolic resource for essential cellular components in microorganisms. Crude glycerol production is reviewed, highlighting relevance in current biodiesel technologies and its biochemical composition. To efficiently utilize waste glycerol, co-valorization with low-cost substrates through biocircular platforms using various microorganisms or insects for second and third-generation oxy-biofuels has been explored. Among these, the black soldier fly larvae have demonstrated higher competitiveness for lipid contents (35–43%), making them a promising organism for recycling waste glycerol into biodiesel production, alongside microalgae and oleaginous yeast. The microbial biodiesel productivity from oleaginous yeast is notably higher (3546 kg ha −1 y −1 ) than soybean biodiesel (562 kg ha −1 y −1 ), while microalgal biodiesel productivity surpasses palm biodiesel by more than 25 times. Remarkably, black soldier fly larvae biodiesel productivity was reported to be ~ 1.7 times higher than microalgae and an impressive ~ 43 times higher than palm biodiesel. Despite their potential for biodiesel production, waste glycerol from biodiesel industry still represents a challenge because of high impurities, high viscosity, and limited direct applications in existing processes. To further enhance energy sustainability and address the challenge of waste glycerol, biocircular platforms are discussed for waste glycerol utilization with domestic wastewater sludge, lignocellulosic biomass, and protein-rich wastes. These platforms offer opportunities to create other sustainable agricultural products while minimizing their environmental footprint.

A closed-loop approach for enhanced biodiesel recovery from rapeseed biodiesel-based byproducts through integrated glycerol recycling by black soldier fly larvae - Adel W. Almutairi; Abdelfatah Abomohra; Mahdy Elsayed (Journal of Cleaner Production, 2023)

Biphasic lignocellulose fractionation for staged production of cellulose nanofibers and reactive lignin nanospheres: A comparative study on their microstructures and effects as chitosan film reinforcing - Meysam Madadi; Mahdy Elsayed; Guojie Song; Rajeev Kumar; Mohamed Mahmoud-Aly; Bikram Basak; Byong-Hun Jeon; Fubao Sun (Chemical Engineering Journal, 2023)

Sustainable lignocellulose fractionation by integrating p-toluenesulfonic acid/pentanol pretreatment with mannitol for efficient production of glucose, native-like lignin, and furfural - Meysam Madadi; Mahdy Elsayed; Fubao Sun; Jing Wang; Keikhosro Karimi; Guojie Song; Meisam Tabatabaei; Mortaza Aghbashlo (Bioresource Technology, 2023)

Efficient removal of Cd (II) from contaminated water and soils using nanoparticles from nitrogen fertilizer industry waste - Elsayed Elkhatib; Ahmed Mahdy; Ayman Mahmoud; Mohamed Moharem (Journal of Environmental Health Science and Engineering, 2019)

Using nanoparticles from water treatment residuals to reduce the mobility and phytoavailability of Cd and Pb in biosolid-amended soils - Elsayed A. Elkhatib; Fatma Sherif; Mahrous Kandil; Ahmed Mahdy; Mohamed Moharem; Abdulla A. Al-Basri (Environmental Geochemistry and Health, 2018)

Green synthesis of nanoparticles by milling residues of water treatment - Elsayed A. Elkhatib; Ahmed M. Mahdy; Karam A. Salama (Environmental Chemistry Letters, 2015)

Veterinary antibiotic resistance, residues, and ecological risks in environmental samples obtained from poultry farms, Egypt - Hesham Dahshan; Amr Mohamed Mohamed Abd-Elall; Ayman Mohamed Megahed; Mahdy A. Abd-El-Kader; Ehab Elsayed Nabawy (Environmental Monitoring and Assessment, 2015)

Effects of drinking water treatment residuals on nickel retention in soils: a macroscopic and thermodynamic study - Elsayed A. Elkhatib; Ahmed M. Mahdy; Mohamed M. ElManeah (Journal of Soils and Sediments, 2013)